School Leadership and Student Motivation - Renchler, Ron.; ERIC Clearinghouse on Educational Management (Eugene, OR : ERIC Clearinghouse on Educational Management, 1992)
School leaders can generate student motivation by creating an atmosphere where academic success and the motivation to learn are expected and rewarded. Leaders can create a school culture conducive to learning by shaping the instructional climate and using activities and symbols to communicate goals. School restructuring that creates a positive psychological environment also influences student motivation. School leaders can create this environment by establishing policies and programs that: stress goal-setting and self-regulation, offer student choice, reward "personal bests," foster teamwork, and teach time management skills. A school's organizational structure is another influence, which can offer intrinsic rewards and enhance student autonomy. School leadership can also promote motivation by demonstrating a school value system that creates consensus around goals related to motivation and achievement. Lessons from the school leader's personal life and from noneducational settings can also be applied to education. Recognizing and rewarding success in all forms is important. (LMI)
Availability: ERIC Clearinghouse on Educational Management, University of Oregon, 1787 Agate Street, Eugene, OR 97403 (free; $2.50 postage and handling).
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: RI88062004.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Educational Environment; Elementary Secondary Education; Goal Orientation; Incentives; Leadership; Motivation Techniques; Organizational Climate; School Culture; Student Motivation; ERIC Digests; ERIC Publications; ERIC Digests in Full Text